Newmark’s Translation Methods in Indonesian Translation of NIKI’s “La La Lost You” - Windi Azahra; Widhiyanto (Journal of English Language Learning, 2025)
Song lyric translation plays a crucial role in enabling audiences to access meaning and emotional expression across languages, particularly within digital platforms such as YouTube. Despite the extensive application of Newmark’s translation methods in translation studies, limited research has specifically examined their use in Indonesian song subtitles distributed through online lyric channels. This study aims to identify the Newmark translation methods employed in the Indonesian subtitles of NIKI’s song “La La Lost You” on the Indolirik YouTube channel and to analyze how these methods convey meaning and emotional nuance from English into Indonesian. Adopting a qualitative descriptive approach, the data were collected from the original English lyrics and their Indonesian subtitles and analyzed using Newmark’s translation method framework. The findings indicate that communicative translation is the most frequently applied method, followed by free translation, semantic translation, and faithful translation. Communicative translation is predominantly utilized to render emotional expressions, idiomatic language, and implicit meanings, while free translation emphasizes emotional states by reducing surface textual elements. Semantic and faithful translations appear in lines with relatively straightforward meanings that require minimal modification. These findings suggest that the translator prioritizes audience comprehension and emotional accessibility, reflecting the influence of YouTube as a digital consumption context and highlighting communicative translation as an effective strategy in digital song subtitling.